Encapsulated Whole Bone Marrow Cells Improve Survival in Wistar Rats after 90% Partial Hepatectomy - Carolina Uribe-Cruz; Carlos Oscar Kieling; Mónica Luján López; Alessandro Osvaldt; Gustavo Ochs de Muñoz; Themis Reverbel da Silveira; Roberto Giugliani; Ursula Matte (Stem Cells International)
Background and Aims. The use of bone marrow cells has been suggested as an alternative treatment for acute liver failure. In this study, we investigate the effect of encapsulated whole bone marrow cells in a liver failure model. Methods. Encapsulated cells or empty capsules were implanted in rats submitted to 90% partial hepatectomy. The survival rate was assessed. Another group was euthanized at 6, 12, 24, 48, and 72 hours after hepatectomy to study expression of cytokines and growth factors. Results. Whole bone marrow group showed a higher than 10 days survival rate compared to empty capsules group. Gene expression related to early phase of liver regeneration at 6 hours after hepatectomy was decreased in encapsulated cells group, whereas genes related to regeneration were increased at 12, 24, and 48 hours. Whole bone marrow group showed lower regeneration rate at 72 hours and higher expression and activity of caspase 3. In contrast, lysosomal-β-glucuronidase activity was elevated in empty capsules group. Conclusions. The results show that encapsulated whole bone marrow cells reduce the expression of genes involved in liver regeneration and increase those responsible for ending hepatocyte division. In addition, these cells favor apoptotic cell death and decrease necrosis, thus increasing survival.